2021
DOI: 10.1016/j.jcf.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Defective BACH1/HO-1 regulatory circuits in cystic fibrosis bronchial epithelial cells

Abstract: Background: The stress-regulated enzyme hemeoxygenase-1 (HO-1) contributes to the cell response towards inflammation and oxidative stress. We previously reported on curtailed HO-1 expression in cystic fibrosis (CF) bronchial epithelial (CFBE41o-) cells and CF-mice, but the molecular mechanisms for this are not known. Here, we compared healthy and CF bronchial epithelial cells for regulatory circuits controlling HO-1 protein levels.Methods: In this study, we employed immunohistochemistry on CF and healthy lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Furthermore, the depth of the crypts in the small intestine of the mice was increased. Studies have shown that DON exposure caused oxidative stress in the intestine, including changes in the mRNA expressions of CAT, GSH-PX, and the serum MDA content, which led to a cascade of intestinal damage. , HO-1 is a well-known antioxidant factor, and several studies have shown that HO-1 plays an anti-inflammatory and antioxidant role, protecting the body from external damage. In the present study, the protein and mRNA levels of HO-1 were found to decrease significantly in the DON-exposed group, which is consistent with previous studies. , Likewise, DON exposure reduced the mRNA levels of CAT and SOD-2 in mouse jejunum. In vitro, the results showed that 0.5–2 μM DON significantly reduced the protein and mRNA expressions of HO-1 and increased ROS generation.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the depth of the crypts in the small intestine of the mice was increased. Studies have shown that DON exposure caused oxidative stress in the intestine, including changes in the mRNA expressions of CAT, GSH-PX, and the serum MDA content, which led to a cascade of intestinal damage. , HO-1 is a well-known antioxidant factor, and several studies have shown that HO-1 plays an anti-inflammatory and antioxidant role, protecting the body from external damage. In the present study, the protein and mRNA levels of HO-1 were found to decrease significantly in the DON-exposed group, which is consistent with previous studies. , Likewise, DON exposure reduced the mRNA levels of CAT and SOD-2 in mouse jejunum. In vitro, the results showed that 0.5–2 μM DON significantly reduced the protein and mRNA expressions of HO-1 and increased ROS generation.…”
Section: Discussionsupporting
confidence: 91%
“…HO-1 has anti-inflammatory, anti-oxidative, anti-apoptotic, and anti-proliferative effects. As an adaptive and protective response to noxious stimuli, the production of HO-1 is closely related to some diseases [ 37 , 38 ]. In this study, CD particles induced an increase in cellular ROS, Ca 2+ , and HO-1 levels, and the effect was more pronounced for CD-NPs than for CD-MPs.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a result of the cells reaching homeostasis while existing under these conditions. However, recent data showed modulation of the increased levels of BACH1 resulting from increased protein stability in CF cells, did not rescue the decreased HMOX1 levels [ 51 ]. This suggests that a defect in the CFTR regulation may have a more complex impact on the BACH1/HMOX1 regulatory axis.…”
Section: Discussionmentioning
confidence: 99%